2009
DOI: 10.1243/09576509jpe787
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady numerical investigation of the effect of wakes with eddy shedding in different axial turbine aerofoils

Abstract: In the past it was found experimentally and numerically that eddy shedding on trailing edges of turbine aerofoils has significant effect on the aerodynamic performance. Aerofoils of gas turbines usually have relatively thick trailing edges for reasons of mechanical integrity, and hence strong unsteady wakes are created. The current investigation considers trailing edges without cooling injection; hence the area of application is limited to the low-and medium-pressure stages of a gas turbine. In this work a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…In conclusion, the results of our and other researchers 9,29,31) calculations have good agreement with experimental data qualitatively, but there are quantitative discrepancies. We think that accurate quantitative prediction of flow quantities, T o and P o , in this region is a real challenge to turbulent model developers.…”
Section: Wakesupporting
confidence: 81%
See 1 more Smart Citation
“…In conclusion, the results of our and other researchers 9,29,31) calculations have good agreement with experimental data qualitatively, but there are quantitative discrepancies. We think that accurate quantitative prediction of flow quantities, T o and P o , in this region is a real challenge to turbulent model developers.…”
Section: Wakesupporting
confidence: 81%
“…Recently, Mokulys et al 31) made calculations using three turbulent models: Baldwin-Lomax, Spalart-Allmaras, and k-!. The turbine cascade and flow conditions are the same as those for CC.…”
Section: Wakementioning
confidence: 99%
“…Ning et al 17 suggests that the vortex-shedding unsteady stresses can be modeled in Navier-Stokes equations to achieve a vortex-shedding time-independent solution. In recent unsteady calculations of the flows in a high subsonic range, uRANS, 18 a delayed detached eddy simulation, 19 and large-eddy simulations (LESs) 6,20 were employed, but none of the uRANS results yielded a good trailing edge pressure distribution. Although the LES was better able to reproduce the trailing edge pressure distribution than uRANS, the mesh used appeared to be too coarse; further, preliminary LES results predicted a poor representation of experimental data at the trailing edge because the near-wall turbulence structure could not be resolved, which made the models of the wake turbulence flow ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease might, however, influence not only the efficiency of the turbine, 2,3 but also the blade excitation 4,5 and the axial force. 6 The importance of the losses generated in the axial clearance in a two-dimensional loss share was shown by Mokulys et al 7 ; their results indicated that these losses were the second highest after the stator profile loss.…”
Section: Introductionmentioning
confidence: 91%
“…The potential field, however, is a more complex function of blade loading, loading position (front, aft, mid), suction side curvature, etc. The influence of the potential field is shown in a study by Mokulys et al 7 indicating that major reductions in the axial clearance losses are possible by changing the rotor loading. This further indicates that different blade loading may lead to changes in the axial clearance-efficiency curve shape.…”
Section: An Example Of the Mixing Loss Evolution Is Plotted Inmentioning
confidence: 98%